(untitled) (Eureka Journal of Artificial Intelligence and Data Innovation, 2026)
In this paper, the problem of generating a spray trajectory for painting uneven surfaces using a robot manipulator, based on surface normal vectors, is studied in the MATLAB environment. On uneven surfaces, it is not sufficient for the spray gun to simply move at a certain distance above the surface; its orientation must also align with the surface normal. Otherwise, the spray angle increases, the paint footprint elongates, and the coating quality deteriorates. In this paper, a model of an uneven surface is created using a sinusoidal function, the trajectory of the spray gun above the surface is generated, and the normal vectors are computed. Furthermore, the distribution of coating thickness over the 3D surface and the coating quality indicators are evaluated using MATLAB. The results demonstrate that an adaptive trajectory based on surface normal vectors plays a crucial role in improving coating quality.